A Remarkable Catalyst Combination to Widen the Operating Temperature Window of the Selective Catalytic Reduction of NO by NH3. Issue 8 (24th July 2014) - Zhang, Runduo; Liu, Ning; Luo, Zhen; Yang, Wei; Liang, Xin; Xu, Ruinian; Chen, Biaohua; Duprez, Daniel; Royer, Sébastien
Abstract The front cover artwork for issue 08/2014 is a collaboration between Beijing University of Chemical Technology (P.R. China) and Poitiers University (France). The image shows the principle on catalyst combination for an ideal autoexhaust control covering a broad temperature range. See the Full Paper itself at dx.doi.org/10.1002/cctc.201402514.